A case of ameloblastic carcinoma of the maxilla treated with a multidisciplinary approach. Issue 1 (January 2023) - Shibata, Akinobu; Kondo, Eiji; Inayoshi, Katsuhito; Kurita, Hiroshi
Abstract: Ameloblastic carcinoma is a malignant odontogenic tumor. Its incidence in Japan is reported to be 0.21 % of all odontogenic tumors; hence, it is extremely rare. In this study, we report a case of multidisciplinary treatment for ameloblastic carcinoma of the maxilla. A 76-year-old man was referred to our hospital because of swelling in his left maxillary gingiva. The left maxillary tumor (47 × 40 mm) was diagnosed as ameloblastic carcinoma. The patient received preoperative chemotherapy (Nedaplatin 100 mg/m 2 and Docetaxel 60 mg/m 2 ), underwent surgery (total maxillary resection, reconstructive surgery with an anterolateral thigh flap, and orbital floor reconstruction with fifth and sixth costal cartilage), and received postoperative radiotherapy (63 Gy/35 fr). There was no recurrence or metastasis 53 months after treatment.